Digital tele-echocardiography: a look inside - Daniele Giansanti; Sandra Morelli (Istituto Superiore di Sanità, 2009)
Digital tele-echocardiography (T-E) has the potentiality to allow relevant change in health care organization. The purpose of the paper is to analyze the scientific development around the digital T-E to explore the successful applications and individuate the limits which hamper the routine introduction in the National Health Care System (NHCS). A literature review was carried out by searching for studies from 1988 to 2008. The studies have been investigated according to four crucial issues: a) the employment of the digital T-E versus the traditional videotape registrations; b) the evolution of the telecommunication network and T-E; c) the quality assessment of the images after transmission; d) the economical legal and social impact of the T-E. The analysis showed a generalized increased diffusion of the digital T-E thanks to the wonderful development of the information technology. This diffusion was sometimes also accompanied by investigation studies on the diagnostic accuracy and on cost-benefit analysis with special care to the economical and social impact. The study examined some points which need to be improved to allow a better introduction of the T-E in the NHCS as a routine exam. Among these two were the most important. The first was the lacking of an easy and automatic methodology for the image quality assessment alternative to the currently used methods which are highly complex, expensive and needing a long time to be applied. The second was the lacking of a properly designed methodology for the health technology assessment in T-E, the latter, as it is well known is a very complex and heterogeneus system embedding parts from telematics, bioengineering, and medical physics.